2016
DOI: 10.1016/j.eurpsy.2016.01.660
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between childhood trauma and theory of mind in schizophrenia

Abstract: IntroductionA history of childhood trauma is reportedly more prevalent in people suffering from psychosis than in the general population. Previous studies linked childhood trauma (CT) to neurocognitive impairments in schizophrenia (SCZ), but rarely to theory of mind (TOM) deficits.ObjectivesTo investigate the relationship between TOM deficits and CT in SCZ.MethodsFifty-eight outpatients with stable SCZ completed the Childhood Trauma Questionnaire retrospectively assessing five types of childhood trauma (emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Higher scores on the CTQ and the aforementioned scales were associated with weaker ToM performance. This appears to be in line with the findings of Mrizak et al ( 46 ), who reported a link between physical neglect in childhood and ToM deficits in schizophrenic patients. The role of physical childhood maltreatment in the ToM performance of opioid dependent patients suggested by this result appears noteworthy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Higher scores on the CTQ and the aforementioned scales were associated with weaker ToM performance. This appears to be in line with the findings of Mrizak et al ( 46 ), who reported a link between physical neglect in childhood and ToM deficits in schizophrenic patients. The role of physical childhood maltreatment in the ToM performance of opioid dependent patients suggested by this result appears noteworthy.…”
Section: Discussionsupporting
confidence: 93%
“…In a sample of chronically depressed patients, amygdala activation during affective ToM tasks was largely modulated by childhood maltreatment and not by pathophysiological correlates of depressive symptoms ( 45 ). In schizophrenic patients, ToM impairements have been associated with physical neglect during childhood ( 46 ) and childhood trauma has been related to alterations in brain functioning during a ToM task ( 47 ). In non-clinical groups, childhood maltreatment has been linked to ToM alterations in both children ( 48 ) and adults ( 49 ).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to social cognition, childhood trauma exposure was not associated with basic facial emotion processing deficits, but was associated with deficits in the most complex ToM tests within the TASIT (i.e., including the understanding of lies and sarcasm) in all groups, regardless of diagnosis. This is consistent with trauma‐related alterations of social cognitive processing previously reported in trauma‐exposed youths (van Schie et al ., ), and in healthy youths (Benarous, Guile, Consoli, & Cohen, ; Luke & Banerjee, ) and adults (Germine et al ., ), as well as in adult patients with chronic PTSD (Nazarov et al ., ) and SZ (Mrizak et al ., 2016b). The present finding that trauma exposure was associated with ToM processes, but not with facial emotion processing, is also consistent with the findings of Germine et al .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, trauma exposure has been associated with schizotypal personality features in non‐clinical populations (Sheinbaum, Kwapil, & Barrantes‐Vidal, ; Velikonja, Fisher, Mason, & Johnson, ). While there has been an increasing interest in understanding the role of trauma in the cognitive deficits of psychotic disorders (Green, Chia, et al ., ; Lysaker, Meyer, Evans, & Marks, ; McCabe, Maloney, Stain, Loughland, & Carr, ; Shannon et al ., ), there has been relatively little investigation of associations between childhood trauma exposure and specifically social cognitive, or schizotypal traits (Mrizak et al ., 2016b; Russo et al ., ; Schurhoff et al ., ). Understanding whether associations exist between early life adversity and these illness‐related factors may assist to determine customized treatments for trauma‐exposed cases; and whether any such associations differ according to diagnosis of SZ or BD was addressed in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation